PENGENALAN ANGKA 1-20 DALAM PENGEMBANGAN KOGNITIF SISWA TK KARTIKA 1-21 PEKANBARU - Nurhaliza Nurhaliza; Inggit Winarsih; Ida Windi Wahyuni (UIR PRESS, 2019)
The development of cognitive abilities is the ability to think of children to develop creativity towards the world around them. This type of research is classroom action research conducted in two cycles. This study aims to evaluate the increase in the ability to recognize the symbol number 1-20 through child worksheets at the age of 5-6 Years at TK Kartika 1-21 Pekanbaru. Research subjects are teachers and children aged 5-6 years with a total of 15 children. Based on the results of the study in spelling out by pointing objects 1-10 there were 10 children (67%) with the criteria of Developing by Expectations (BSH), then in appointing a symbol of 1-20 there were 9 children (60%) with the criteria of Developing Accordance with Expectations (BSH), and in connecting or pairing 1-10 symbols there are 10 children (67%) with the criteria of Developing by Expectations (BSH) and this shows that the ability to recognize numbers 1-20 in TK Kartika 1-21 Pekanbaru has met the criteria well.